Pengaruh Integrasi Praktik Manajemen dan Pemanfaatan Teknologi Informasi terhadap Kinerja Seller Marketplace di Indonesia - Riscki Elita Rosihana (Jurnal Ragam Pengabdian, 2026)
This study examines the role of management practices and information technology utilization in shaping seller performance within digital marketplace platforms in Indonesia. The research adopts a quantitative approach by conducting a survey of 44 active sellers who meet the predefined criteria. Data were analyzed using multiple linear regression to assess both individual and combined effects of the examined variables. The findings indicate that management practices contribute positively to seller performance, while the utilization of information technology demonstrates a stronger influence. When considered jointly, the integration of managerial capabilities and digital system usage explains a substantial proportion of variation in seller performance, as reflected by a coefficient of determination (R²) of 0.625. These results highlight that improving seller performance in digital marketplaces requires not only structured operational management but also the effective use of relevant digital technologies.